Mainstreaming the Re-orientation Approach in Communication Education: Nepal’s Perspective - Nirmala Mani Adhikary (Politeknik Negeri Bali, 2018)
Though communication education in Nepal is largely remained focused on exogenous source(s) for long time ongoing endeavors in the recent years – especially in the field of communication theory – have been forwarding the agenda of paradigm shift in communication discipline. The ongoing paradigm shift is looking beyond de-Westernization and forwarding the notion of Re-orientation. De-Westernization has been the dominant perspective while critiquing the theorization of communication, but there needs Re-orientation for re-centering indigenous perspectives in any discipline. Hence, it is pertinent to observe and promote the re-orientation initiatives in the discipline. Drawing on instances both from the East and the West, an appraisal on contemporary endeavors to re-orient communication theory towards philosophical and cultural heritage of Nepal has been presented.